WORD-FORMATION IN ENGLISH AGRICULTURAL TERMINOLOGY: A LINGUISTIC AND FUNCTIONAL PERSPECTIVE - Xamidov Mirmuxsin Mirolimovich (Western European Studies, 2025)
This article examines the main word-formation mechanisms in English agricultural terminology. It focuses on derivation, compounding, conversion, abbreviation, and borrowing as the primary means of creating terms in the agricultural domain. The study uses examples from glossaries, academic texts, and databases to illustrate how such processes serve both linguistic efficiency and scientific clarity. The research contributes to applied linguistics and terminology, and is relevant for educators, translators, and specialists working in agrarian studies.
Keywords: agricultural terminology; word-formation; derivation